Evaluation of peri‐implant tissues condition after 10–15 years of loading in treated chronic periodontitis patients attending a private practice setting: A retrospective study. Issue 4 (27th January 2021) - Guarnieri, Renzo; Di Nardo, Dario; Di Giorgio, Gianni; Miccoli, Gabriele; Testarelli, Luca
Abstract: Objectives: To retrospectively evaluate the conditions of the peri‐implant tissues in treated patients with chronic periodontitis (CP) and in patients without chronic periodontitis (noCP). Materials and methods: A chart review was used to evaluate 267 implants, 134 placed in 42 CP treated patients and 133 placed in 46 noCP patients. The primary outcome was to evaluate the condition of the peri‐implant tissues (health, peri‐mucositis, and peri‐implantitis). The secondary outcome was to evaluate the possible association of some variables, such as, Plaque Index (PI), Bleeding Index (BI), probing pocket depth (PD), bleeding on probing (BoP), bone level (BL), loading time, type of implant placement and loading protocol, type of prosthesis, type of bone, implant manufacturer, and implant diameter and length, with the implant health condition. Results: The analysis of patient files revealed that after 10–15 years of loading (mean loading time 13.4 ± 2.07 years), six noCP patients (13%) experienced implant loss with a total of nine implants (6.7%) lost. The remaining 124 implants were classified: 54 (43.5%) as healthy, 45 (36.3%) with peri‐implant mucositis, and 25 (20.2%) with peri‐implantitis. Twelve CP subjects (28.5%) experienced implant loss with a total of 19 implants (14.1%) lost. The remaining 115 implants were classified: 34 (29.5%) as healthy, 40 (34.7%) with peri‐implant mucositis and 41 (35.6%) with peri‐implantitis. Compared with noCP subjects, only treated CP subjects with recurrent periodontal disease (RPD) showed differences statistically significant ( p < .05). Conclusions: After 10–15 years of loading, in CP patients treated in a private practice setting, most implants (70.1%) were classified with some type of peri‐implant inflammation. In patients with RPD, a higher tendency for implant loss and peri‐implant biologic complications was found.